A Hospital Based Study on Estimation of Adenosine Deaminase Activity (ADA) in Cerebrospinal Fluid (CSF) in Various Types of Meningitis - Ashok Kumar Agarwal; Sonia Bansal; Vidya Nand (Journal of Clinical and Diagnostic Research, 2014)
Objective: Tuberculosis kills 3.70 lakh patients in India every year,out of which 7-12 % are meningeal involvement. Delay in its diagnosis and initiation of treatment results in poor prognosis and squeal in up to 25% of cases. The aim of the present study is to look for a simple, rapid, cost effective, and fairly specific test in differentiating tubercular aetiology from other causes of meningitis. In the present study we measured the adenosine deaminase activity (ADA) in Cerebrospinal Fluid (CSF) of Tubercular Meningitis (TBM) and non-TBM patients. Methods: Fifty six patients attending hospital with symptoms and signs of meningitis were selected and divided into three groups: tubercular, pyogenic, and aseptic meningitis, depending upon the accepted criteria. CSF was drawn and ADA estimated. Results: Out of 32 tubercular patients, 28 had CSF-ADA at or above the cut-off value while four had below. Out of 24 nontuberculous patients (pyogenic and aseptic meningitis), two aseptic meningitis (AM) patient had ADA levels at or above the cut-off value while 22 had below this value. Results of our study indicate that ADA level estimation in CSF is not only of considerable value in the diagnosis of TBM, CSF, and ADA level 10 U/L as a cut-off value with sensitivity 87.5% and specificity 83.33% and positive predictive value of the test was 87.5%.and 83.3% negative predictive value. Conclusion: It can be concluded that ADA estimation in CSF is not only simple, inexpensive and rapid but also fairly specific method for making a diagnosis of tuberculous aetiology in TBM, especially when there is a dilemma of differentiating the tuberculous aetiology from non-tuberculous ones. For this reason ADA estimation in TBM may find a place as a routine investigation.